Heating and Evaporation of Droplets of Multicomponent Aqueous Suspensions with Solid Insoluble Impurities of Different Thermophysical Properties - Kerimbekova S. A. Susanna Aleksandrovna; Kuznetsov G. V. Geny Vladimirovich; Shakhray M. S. Mikhail Sergeevich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen